Association of Combined p73 and p53 Genetic Variants with Tumor HPV16-Positive Oropharyngeal Cancer - Wang, Zhongqiu; Sturgis, Erich M.; Guo, Wei; Song, Xicheng; Zhang, Fenghua; Xu, Li; Wei, Qingyi; Li, Guojun (PLOS ONE, 2012)
p53 and p73 interact with human papillomavirus (HPV) E6 and E7 oncoproteins. The interplay between p53 and p73 and HPV16 may lead to deregulation of cell cycle and apoptosis, through which inflammation/immune responses control the HPV clearance and escape of immune surveillance, and subsequently contribute to tumor HPV16 status. In this case-case comparison study, HPV16 status in tumor specimens was analyzed and p53 codon 72 and p73 G4C14-to-A4T14 polymorphisms were genotyped using genomic DNA from blood of 309 oropharyngeal cancer patients. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated in univariate and multivariable logistic regression models to examine the association. The results from this study showed both p53 variant genotypes (Arg/Pro+Pro/Pro) and p73 variant genotypes (GC/AT+AT/AT) were significantly associated with HPV16-positive tumor in oropharyngeal cancer patients (OR, 1.9, 95% CI, 1.1–3.3 and OR, 2.1, 95% CI, 1.2–3.8, respectively), while the combined variant genotypes (p53 Pro carriers and p73 AT carriers) exhibited a significantly greater association with HPV16-positive tumor (OR, 3.2, 95% CI, 1.4–7.4), compared with combined wild-type genotypes (p53 Arg/Arg and p73 GC/GC), and the association was in a statistically significant dose-effect relationship (p = 0.001). Moreover, such association was more pronounced among several subgroups. These findings suggest that variant genotypes of p53 and p73 genes may be individually, or more likely jointly, associated with tumor HPV16-positive oropharyngeal cancer patients, particularly in never smokers. Identification of such susceptible biomarkers would greatly influence on individualized treatment for an improved prognosis.